The food security: are we warned? / Aqilah Hanani Musa ... [et al.] - Musa, Aqilah Hanani; Md Rudin, Haifa Hazirah; Lut, Lutfiah Hazwani; Mustaza, Syaza Adriana; Abu Shah, Nor'aishah (UiTM Cawangan Negeri Sembilan, 2022)
Food security is the measure of the availability of food and a person's ability to access it. According to United Nations' Committee on World Food Security, it is stated that food security is defined as all people in which at all times; have physical, social, and economic access to sufficient, safe, and nutritious foods according to their food preferences and dietary needs for an active and healthy life. The evolution of worldwide technology today has proved that there are various ways to ensure that foods are safe to eat and easy to access for people. Many years ago, people had to work harder and strive just to make sure that they could sustain the ability to get food supply for their families and themselves. One of the main importance of global food security is to provide nutritious and quality food, which is easy to access, and it is fundamental to human existence. With better security access to food, it can produce a wide range of positive impacts.